Lateral Retinaculum Lengthening and Medial Patellofemoral Ligament Reconstruction With Adductor Sling Technique - Juan Pablo Martinez-Cano MD, MSc; Maria Antonia Gomez-Sierra MD; Andreu Castelo MD; Fernando Manuel Mejía MD (SAGE Publishing, 2021)
Background: There are multiple ways of reconstructing the medial patellofemoral ligament (MPFL), including dynamic techniques that fix the graft to the adductor magnus tendon. We present this technique associated to an increasingly common surgery used as adjuvant in some patients with patellar instability, lateral retinaculum lengthening. Indications: Recurrent patellar dislocation with medial laxity and lateral tightness/lateral tilt. Technique Description: This is double bundle MPFL reconstruction with anterior tibialis tendon allograft. Both autograft or allograft may be used, with a minimum length of 15 cm. The graft is fixed to the proximal third of the patella, passing as a sling under the adductor magnus tendon where it is fixed with sutures and returns to the patella. The patellar fixation includes a 10 to 15 mm deep and 4 to 4.5 mm diameter tunnel in the proximal third with suture stitches to the soft tissues in the entrance of the tunnel, plus an anterior periostic tunnel for the second bundle in the proximal third of the patella fixed with suture stitches. Meanwhile, the lateral retinaculum is incised longitudinally into a superficial and deep layer, in order to lengthen it the desired length. Results: The expected outcome of the procedure is to have a stable patellofemoral joint, with patients that gain the lost function and may return to sport without recurrence of patellar dislocation. Discussion/Conclusion: This is a simple, cheap, and reproducible technique that corrects both medial laxity and lateral tightness for patients with recurrent patellar dislocation.